2022
DOI: 10.36351/pjo.v38i4.1378
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Dry Eyes after Cataract Surgery and Effect of Gender, Duration of Cataract and Age on Dry Eye Symptoms after Phacoemulsification

Abstract: Purpose:  To determine the frequency of dry eyes in patients after cataract surgery and to find out the effect of gender, duration of cataract and age on dry eye symptoms after phacoemulsification. Study Design:  Descriptive Observational study. Place and Duration of Study:  Layton Rehmatulla Benevolent Trust Free Eye and Cancer Hospital, Lahore from October 2015 to April 2016. Methods:  One hundred and twenty patients between 40-80 years of age and suffering from cataract were included. Past medical history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…These findings were consistent with the results of a study conducted by Rahim et al 21 in which it was reported that overall frequency of "dry eye disease" was 29.2%. Similar results were observed in a study conducted by Hamad et al 16 who reported that A. Anwar, M. M. Chaudhry, S. Ahmed et al P J M H S Vol.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings were consistent with the results of a study conducted by Rahim et al 21 in which it was reported that overall frequency of "dry eye disease" was 29.2%. Similar results were observed in a study conducted by Hamad et al 16 who reported that A. Anwar, M. M. Chaudhry, S. Ahmed et al P J M H S Vol.…”
Section: Discussionsupporting
confidence: 93%
“…Cataract surgery by phacoemulsification is one of the commonest surgical procedure that is performed in the field of ophthalmology. It has been found associated with many complications including corneal edema 18 , increased intraocular pressure that may lead to glaucoma 19 , incomplete recovery of visual acuity 19 , intraocular lens drop 20 and dry eye disease 21 . "Dry eye disease" occurs secondary to changes in the "ocular surface" and the "tear film" that are induced by the cataract surgery by phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%